Systemic neuroimmune responses in people with non-specific neck pain and cervical radiculopathy, and associations with clinical, psychological, and lifestyle factors - Lutke Schipholt, Ivo J.; Scholten-Peeters, Gwendolyne G. M.; Koop, Meghan A.; Bonnet, Petra; Bontkes, Hetty J.; Coppieters, Michel W. (Frontiers in Molecular Neuroscience, 2022)
Neuroimmune responses remain understudied in people with neck pain. This study aimed to (1) compare a broad range of systemic neuroimmune responses in people with non-specific neck pain (N=112), cervical radiculopathy (N=25) and healthy participants (N=23); and (2) explore their associations with clinical, psychological and lifestyle factors. Quantification of systemic neuroimmune responses involved ex-vivo serum and in-vitro evoked-release levels of inflammatory markers, and characterisation of white blood cell phenotypes. Inflammatory indices were calculated to obtain a measure of total immune status and were considered the main outcomes. Differences between groups were tested using ANCOVA and multivariable regression models. Compared to healthy participants, the ex-vivo pro-inflammatory index was increased in people with non-specific neck pain (β=0.70, p=0.004) and people with cervical radiculopathy (β=0.64, p=0.04). There was no difference between non-specific neck pain and cervical radiculopathy (β=0.23, p=0.36). Compared to non-specific neck pain, people with cervical radiculopathy showed lower numbers of monocytes (β=-59, p=0.01). There were no differences between groups following in-vitro whole blood stimulation (p≥0.23) or other differences in the number and phenotype of white blood cells (p≥0.07). The elevated ex-vivo neuroimmune responses in people with non-specific neck pain and radiculopathy support the contention that these conditions encompass inflammatory components that can be measured systemically. There were multiple significant associations with clinical, psychological and lifestyle factors, such as pain intensity (β=0.25) and anxiety (β=0.23) in non-specific neck pain, visceral adipose tissue (β=0.43) and magnification (β=0.59) in cervical radiculopathy, and smoking (β=0.59) and visceral adipose tissue (β=0.52) in healthy participants. These associations were modified by sex, indicating different neuroimmune associations for females and males.